Analisis Komparatif Vokal Bahasa Arab dan Bahasa Inggris - Iisrohli Irawati Irawati; Lini Oktiasari (LPPM Press, 2012)
Abstract:Every language has own structure and unic. Every language is also different between one andothers. This study is compare between English and Arabic vocal. This study to accomodate whowants to know more about English and Arabic.This study use comparative analysis and study ofphonology. English vowel sounds are described according to criteria which are: frontness – backness,closeness – openness, and lip – rounding. and contrast, in Arabic phonetics we describe soundsaccording to criteria which are: fathah, dhammah dan kasrah and long vowal like ma>d, alif, wauand ya’